Alcoholism prevention and recovery - an Orthodox overview - Andrei, Constantin (Technium Social Sciences Journal, 2023)
Alcohol produces devastating consequences on the human being and on society as a whole, starting with medical problems that directly affect the consumer, continuing with problems of a social nature (affecting the consumer’s family as well), economic problems (regarding the amounts of money spent on the purchase of alcohol, but also problems related to the workplace), as well as problems of a legal nature (increased rate of divorces, the commission of traffic offenses or domestic violence, neglect of children, but also manslaughter or intentional murder), but especially of spiritual order (breaking the connection with God and deepening more and more into sin).